In vivo vascularized scaffold with different shear-exposed models for lymphatic tissue regeneration - Hsiao, Hui-Yi; Mackert, Gina A.; Chang, Yung-Chun; Liu, Jia-Wei; Chang, Frank Chun-Shin; Huang, Jung-Ju (Journal of tissue engineering, 2023)
Current clinical treatments on lymphedema provide promising results, but also result in donor site morbidities. The establishment of a microenvironment optimized for lymphangiogenesis can be an alternative way to enhance lymphatic tissue formation. Hemodynamic flow stimuli have been confirmed to have an influential effect on angiogenesis in tissue engineering, but not on lymphatic vessel formation. Here, the three in vivo scaffolds generated from different blood stimuli in the subcutaneous layer, in the flow through pedicle, and in an arterio-venous (AV) loop model, were created to investigate potential of lymphangiogenesis of scaffolds containing lymphatic endothelial cells (LECs). Our results indicated that AV loop model displayed better lymphangiogenesis in comparison to the other two models with slower flow or no stimuli. Other than hemodynamic force, the supplement of LECs is required for lymphatic vessel regeneration. The in vivo scaffold generated from AV loop model provides an effective approach for engineering lymphatic tissue in the clinical treatment of lymphedema.
Gesehen am 30.10.2023